PERAN GURU MATA PELAJARAN IPS DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Maldini, Polo; Aminuyati, Aminuyati; Okianna, Okianna (Universitas Tanjungpura, 2024)
This study aims to identify the factors that influence students' interest in learning and to know the role and efforts of social studies teachers in increasing students' learning interest in class VIII C of SMPN 1 Jawai. The research method applied is descriptive with a qualitative research form. Informants in this study were class VIII C students and a social studies teacher. Data were collected through observation, interviews, and documentation using observation guidelines, interview guidelines, and documentation tools. Based on the data, (1) the role of the social studies teacher includes being a motivator, demonstrator, class manager, mediator, facilitator, and evaluator. (2) The lack of students' interest in learning is caused by internal and external factors. Internal factors include aspects of intelligence, attention, feelings, and interest. Meanwhile, external factors include family and school aspects in facilities and infrastructure. (3) Efforts made by teachers to overcome students' lack of interest in learning include providing motivation, using various learning methods, and giving appreciation to students.